Waves in Cycle: The protests against anti-contagion measures and vaccination in Covid-19 times in Italy - della Porta, Donatella; Lavizzari, Anna (PARTECIPAZIONE E CONFLITTO, 2023)
Since the beginning of the pandemic, while progressive movements have mainly focused on social inequalities exacerbated by the sanitary emergency, a number of protests emerged and quickly became visible that initially targeted the policies taken to reduce contagion and subsequently focused on the vaccine and vaccination. In the attempt to account for the rapid development of these protests, social scientists have mostly turned to classical approaches used in the analysis of far-right organizations and sects, looking at broad transformations in society or at fear and a sense of insecurity at the individual level. In this article, we build upon a social movement approach to look at the main characteristics of the protests against anti-contagion measures. From a theoretical point of view, we point to the importance of disentangling the specific waves happening within broader protest cycles. Empirically, focusing on the Italian case, we present a novel development in protest event analysis looking at the specific forms of action, the actors involved, and their claims in two waves of contention during the pandemic in Italy, between 2020 and 2021.